Theoretical And Practical Pedagogical Bases of Formation of Professional Culture of Students of Military Education - Turgunboyev Toxir; Yusupov Arabboy; Gofforov Zuxriddin; Goipov Abdurauf (Periodica Journal, 2022)
In the process of forming a moral and ethical culture in students of military education, the national ideology, based on the national idea, founded by the President of the Republic of Uzbekistan, has served as a guideline. Islam Karimov recalls that “in the process of forming an ideology, first of all, the progressive worldview, the mentality of this part of the society, which sees its destiny as separate from the destiny of the Motherland, is taking place in the life of the country today. We wholeheartedly support the process and fight for its future.
Keywords: founded; ideology; Motherland; worldview